Kajian Kepatuhan Sarana Produksi Minyak Goreng Sawit di Wilayah Kerja BBPOM di Bandung dan BBPOM di Surabaya dalam Melakukan Fortifikasi Vitamin A - Utami, Setyo; Andriany , Dinny (Badan Pengawas Obat dan Makanan, 2024)
Vitamin A deficiency (VAD) remains a public health issue in many countries, including Indonesia. To address this, the government has mandated vitamin A fortification in food, with cooking oil being a key target. The policy is outlined in SNI 7709-2019 through Minister of Industry Regulation Number 46 of 2019, requiring producers to achieve a minimum vitamin A level of 45 IU/g in fortified cooking oil. Samples of palm cooking oil were collected from producers and packers for evaluation. This study examines the compliance of palm cooking oil production facilities within the Bandung and Surabaya catchment areas under the supervision of THE INDONESIAN FDA REGIONAL OFFICE. Using a descriptive qualitative method, data were collected from sampling and testing conducted between 2021 and 2023, following the Guidelines for Sampling and Testing of Drugs and Food. The results indicate that 31.58% of production facilities failed to meet fortification requirements due to a lack of commitment from producers and limited availability of vitamin A as a fortifier. Non-compliance was linked to facility type, with relaxation of regulations during rising cooking oil prices contributing to the issue. Notably, the fortification program was temporarily paused in January 2022 due to these challenges. To ensure public health benefits, it is essential to reinstate and enforce the vitamin A fortification program for palm cooking oil, emphasizing producer accountability and stable raw material supply.